(untitled) (Al-Qamar, 2021)
This article deals with the inquiry of traditions by Mawlānā Mawdūdī in his Tafsīr Tafheem al-Quran. It finds that Mawlānā Mawdūdī evaluates the hadith by presenting it to the Quran and criticizes the traditions that appear against the Quran, even if they are narrated in Bukhārī and Muslim. At some places, he seems to accept weak traditions whose text does not contradict the Quran instead of the traditions that are considered to be more correct but contradictory to the Quran. Criticizing the Isrāīlī traditions in some places, he calls them an addition to Islam. In some places, mentioning the differences between the sayings of the Imams he proves that such and such a ruling is speculative and Ijtihādī not Manṣūṣ.